PENGEMBANGAN MEDIA PEMBELAJARAN MUHADATSAH BERBASIS POWTOON: Studi Kasus Siswa Kelas VII Mts Nurul Islam Indonesia - Ryzka Aulia; Akmal Walad Ahkas (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
This research was aimed at developing instructional media based PowToon in Muhadatsah education at Mts Nurul Islam Indonesia. Data was collected through interview, observation, dokumentation and test. The collected data wasanalyzed quantitative description. Introduction result obtained through interview and observation. And then questionnaire data related to product validity were analyzed using descriptive analysis. The research reveals that instructional media based PowToon was valid according to bothsome experts, practicable, and has a potential effect to increase student understanding of course content